Performer's voices across centuries and cultures: Selected proceedings of the 2009 performer's voice international symposium - Marshman, Anne (London Imperial college press, 2012)
This book and its accompanying website present the selected proceedings of the inaugural, "The Performer's Voice: An International Forum for Music Performance and Scholarship", directed by Dr Anne Marshman (editor) and hosted by the Yong Siew Toh Conservatory of Music, National University of Singapore. The chapters, which were selected through a process of international peer review, reflect the symposium's wide-ranging interdisciplinary scope, coupled with an uncompromising emphasis on the act of performance, the role of the performer and the professional performer's perspective.